DISINHERITANCE ON THE GROUND OF AN OFFENCE AGAINST A TESTATOR’S NEXT OF KIN (ARTICLE 1008(2)OF THE CIVIL CODE) - Wolak, Grzegorz (Review of European and Comparative Law, 2020)
The article addresses the cause of disinheritance based on an offence against life, health or liberty or of a gross affront to dignity of a testator’s next of kin (Arti-cle 1008(2) of the Civil Code) . Certainly, due to limited space, the subject is far from exhausted . The mere presentation – from both the objective and subjective perspective – of the types of offences whose commitment by an individual holding a right to legitime (forced heir) justifies their disinheritance by the testator would most likely fill up a separate monograph work . Consequently, the author focuses on some most debatable issues related to the subject matter .